Determination of Terrestrial Radiation Level of Obite, Rivers State - Chikaike, Eugene; Kamara, Briggs; Ari, Tamunobereton (Journal of Physical Sciences, 2022)
Purpose: The perceived implication of increase in background radiation level of Obite Community due to inputs of hydrocarbon leakages and its emissions, lead to this research work, which investigated the background ionizing radiation levels of the area. Methodology: An in-situ background ionizing radiation measurement was carried out using radiation meter (Digilert 200) at an elevation of 1.0m above ground level with a Global Positioning System (G.P.S) for geographical location. Results: The background ionizing radiation (BIR) results obtained, varies from 0.007 to 0.024 (mR/hr) with a mean value of 0.013 (mR/hr). The values of Absorbed Dose Rate ranges from 60.9 to 208.0 nGy/hr with a mean value of 115.10±0.003 nGy/hr, which is higher than the recommended safe limit of 84.0 nGy/hr (UNCEAR, 2018). The Annual Effective Dose Equivalent (AEDE) varies from 0.009 to 0.38 mSv/yr with mean of 0.198 mSv/yr, is lower than the safe limit of 1.0 mSv/yr stipulated by ICRP (2003) and WHO (2008). The Excess Lifetime Cancer Risk (ELCR) values ranges from 0.32 to 0.09 x 101 with a mean of 0.062 x 10-1, is higher than the ICRP standard of 0.29 x 10-3 (ICRP, 2003). Conclusions: These results indicate an increase in cancer risk for individuals within the study area. The results were also summarized using the contour map to show various areas of high radiation distributions with interpretation of variability in concentration, in relation to geographical locations within the study area.